The Labanoras’ Hoard of Prague Groats - Smilgevičius, Vytautas (Archaeologia Lituana, 2001)
In this article, the author discusses the hoard of Prague groats of Wenzel IV and the early Lithuanian coins, found in Labanoras (Švenčioniai district). The hoard consists of 5 Prague groats of Charles I, 393 Prague groats of Wenzel IV and I forgery of Prague groat of Wenzel IV. Currently, 2 groats of Charles I, 141 groat of Wenzel IV and the forged groat are in the National museum of Lithuania, 2 groats of Charles I, 180 groats of Wenzel IV – in the Nalšia museum (Švenčionys) and 1 groat of Charles I and 72 groats of Wenzel IV – in the museum of Utena.The Prague groats of Charles I are classified according to the typology of V. Pinta. Only latest varieties, dated 1370–1378, are found in this hoard. The Prague groats of Wenzel IV are classified according to the system of S. Veselý. Thus, the system of three ordinations is used. I ordination is dated 1378–1386 and in the Labanoras’ hoard consists of 5 coins; II ordination is dated 1405–1407 and consists of 27 coins; III ordination is dated 1407–1419 and consists of 61 coin. The mintage of the coins from III ordination could probably been continued by Hussits in 1419–1430. The author states that the process of “seigern” – thesauration of heavier coins and putting into circulation lighter ones – did exist. This process in the territory of the Grand Duchy of Lithuania could begin about 1405–1407, but ended about 1407–1419. This could be proved by the presence of forgery with a weight of 3.18 g, i.e. imitating heavy coin.The hoard is dated of 7-ies of the XV century according to the presence of deniers of Vytautas and Kazimieras. The author doubts if this hoard was hidden in the 3-ies of the XV century, when the situation the Grand Duchy was in the state of civil war – in that time the deniers of Kazimieras did not exist.Finally, the author discusses the circulation of the Prague groats in the teritory of Lithuania. He finds that the Prague groats of 1405–1407 and 1407–1419 emissions were wide spread throughout the Lithuania. Groats of earlier emissions did not spread wide due to their good quality.